A survey of windows based honeypots and program for honeypot log analysis / Asma Raayatiezhad - Raayatiezhad, Asma (2011)
Honeypots are computers that attract attackers to penetrate itself. They are security tools for monitor and identify unauthorized activity. The value of Honeypots is in being hacked. They don‟t have any data, so any traffic to or from them is most unauthorized activity. In fact Honeypots are computers or networks trap, designed to attract and detect malicious attacks. The main goal of this paper is to point out the well known characteristics of Honeypots based on windows platform, design an environment which will allow us to test these characteristics and discuss the results. An implementation of such environment will be tested and analyzed. This work gives a good idea to collect data and the logs which are retrieved and stored in a database for further analysis.